Performance Of Village Officials In Administrative Services In Kajulangko Village, Ampana Tete Sub-District,Entojo Una-Una District, Central Sulawesi Province - Sofyaningsih Muhlis Hasan; Lisda Van Gobel; Lutfia Bakari (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This study aims to determine the Performance of Village Officials in Administrative Services in Kajulangko Village, Ampana Tete District, Tojo Una-Una Regency, Central Sulawesi Province. This research method uses descriptive qualitative research. The data collection techniques used are observation, interview, and documentation techniques. In accordance with the type of research used is qualitative analysis techniques. The results of the research are in the form of the results of interviews conducted with research informants, related to the sub-focus used to be able to know the Performance of Village Officials in Administrative Services in Kajulangko Village, Ampana Tete District, Tojo Una-una Regency. The sub-focuses used are Responsiveness, Justice and Certainty of time. Based on data collection through in-depth interviews, observation, and documentation, each sub-focus is described as follows. Based on the overall interview results above, it can be concluded that the responsiveness of the performance of village officials in providing administrative services is not yet optimal. Based on the results of the interviews, it can be concluded that the performance of village officials in providing administrative services cannot be said to be optimal and in accordance with applicable standards of justice because there are differences in the treatment of individuals from various social and economic backgrounds although there are efforts to achieve equitable justice, there are still many challenges and obstacles that must be overcome. Based on the overall results of the interviews above, it can be concluded that the certainty of the performance of village officials in providing administrative services is not optimal.